Bioluminescent magnetic nanoparticles as potential imaging agents for mammalian spermatozoa. Issue 1 (December 2016) - Vasquez, Erick; Feugang, Jean; Willard, Scott; Ryan, Peter; Walters, Keisha
Abstract Background Nanoparticles have emerged as key materials for developing applications in nanomedicine, nanobiotechnology, bioimaging and theranostics. Existing bioimaging technologies include bioluminescent resonance energy transfer-conjugated quantum dots (BRET-QDs). Despite the current use of BRET-QDs for bioimaging, there are strong concerns about QD nanocomposites containing cadmium which exhibits potential cellular toxicity. Results In this study, bioluminescent composites comprised of magnetic nanoparticles and firefly luciferase (Photinus pyralis ) are examined as potential light-emitting agents for imaging, detection, and tracking mammalian spermatozoa. Characterization was carried out using infrared spectroscopy, TEM and cryo-TEM imaging, and ζ-potential measurements to demonstrate the successful preparation of these nanocomposites. Binding interactions between the synthesized nanoparticles and spermatozoon were characterized using confocal and atomic/magnetic force microscopy. Bioluminescence imaging and UV–visible-NIR microscopy results showed light emission from sperm samples incubated with the firefly luciferase-modified nanoparticles. Therefore, these newly synthesized luciferase-modified magnetic nanoparticles show promise as substitutes for QD labeling, and can potentially also be used for in vivo manipulation and tracking, as well as MRI techniques. Conclusions These preliminary data indicate that luciferase-magnetic nanoparticle composites can potentially be used for spermatozoa detection and imaging. Their magnetic properties add additional functionality to allow for manipulation, sorting, or tracking of cells using magnetic techniques.